Ethnic National and Regional Challenge to Peace Keeping and Development in West Africa ECOMOG in Focus - Okezie Easther Chiamaka; Joseph Bamidele; Paul Anyaogu (MultiTech Publisher, 2023)
The Liberian crisis which is the subject of this study was one of such cases in which the measures was applied to maintain peace by the Economic Community of West Africa State (ECOWAS). The Liberians crisis escalated in 1980 when Samuel Doe staged a coup that brought the ethnic majority of the Liberian to power. The conflict assumed a wider dimension following the involvement of other extraneous forces around Liberians, a situation which the ECOWAS leaders thought would lead to the war spreading to other countries in the sub region. This study examined the operations of the peacekeeping body the ECOMOG which ECOWAS established for the purpose of securing peace in Liberia. For its explanatory tool, the study adopted the theory of collective Security. The major findings of the study include the fact that the domination of political power by the Afro-America Liberians is at the root of the conflict in the country. The study also discovered that poor funding and the colonial orientations of the various forces contributing states in ECOWAS adversely affected the operation of ECOMOG in Liberia. The study recommends that the Leaders of ECOWAS should establish more integrated peacekeeping forces with training in language and cultures of the Nations in the sub-region.